La posibilidad de la "acción libre" en las disertaciones de Epicteto - Braicovich, Rodrigo Sebastián (Revista de Filosofía, 2008)
The aim of this paper is to analyse two alternatives which are present in Epictetus’ Dissertations as possible ways to reach freedom and happiness: a) to identify our will with the will of the divinity; b) to focus exclusively on "what depends on us". Since both paths seem to lead to solipsism and passiveness, we shall offer an alternative interpretation that can reconcile both strategies with the practical approach of the Epictetus’s ethics.